Development of an Instrument to Test Understanding Kinematic Concepts - Jeffry Handhika; Mislan Sasono; Farida Huriawati; Mukholiffatul Maisaroh; Johan Aritonang (UNIVERISTAS PGRI MADIUN, 2023)
This research aims to develop an instrument for understanding kinematics concepts. Instrument development was carried out by adapting the steps (1) Writing specifications and Writing concept understanding test questions (2) Reviewing and improving concept understanding test questions (3) Implementing test questions, (4) Interpreting the results of concept understanding test analysis. The material, construction and language aspects have been declared appropriate by experts. The test was tested on students who had taken basic physics and had teaching/field work experience. Based on the results of trials using Iteman, information was obtained that thirty questions on the concept understanding test were reliable, but six questions were declared invalid. The results of the software analysis also indicate that invalid questions tend to have poor power discrimination and distracting questions below 5%.